The Effect of Increase in Pronation of Rearfoot on Physical Performance - Caner Karartı; Sevil Bilgin; Öznur Büyükturan; Buket Büyükturan (Hacettepe University, 2018)
Objective: Increased pronation in rearfoot can affect daily living activities such as doing sports, long standing and walking and physical fitness of people by disrupting biomechanics of foot. The aim of this study is to examine the relationship between increased pronation in rearfoot and physical performance in young adults. Material and Methods: 64 healthy young adults aged between 18 to 25 years were included in the study voluntarily. The demographic information of the subjects participating in the study was recorded. Rearfoot pronation was assessed by "navicular drop test". The physical performances of the individuals were assessed by "vertical jump test", "side step test" and "shuttle running test". Relationship between rearfoot pronation and physical performance was analyzed. Results: Significant relationship was found between the "navicular drop test" and "side step test" and "shuttle running test" (p <0.05). It was observed that while the severity of rearfoot pronation of individuals increased, "side step" and "shuttle running test" performances were worsened. There was no significant relationship between the "navicular drop test" and "vertical jump test" (p˃0.05). Conclusion: Increased rearfoot pronation negatively affects physical performance of individuals such as leap and running. Early prevention of increased pronation, which is common in young adults, and prevention of possible musculoskeletal anomalies in the future and prevention of decrease in physical performance are important issues to be consider in therapeutic programs.